Sex-Based Differences in the In Vitro Digestibility of MCT Emulsions Stabilized by Various Emulsifiers - Mijal Perez; Carmit Shani Levi; Uri Lesmes (Foods)
Consumer sex influences phenotypic differences in digestive functions that may underlie variations in food disintegration. This study used an in vitro digestion model to test the hypothesis that emulsions follow distinct digestive pathways in men and women. Model emulsions were prepared using medium-chain triglycerides stabilized by beta-lactoglobulin, alpha-lactalbumin, or lactoferrin, and by three non-protein emulsifiers: Tween 80, lecithin, and sucrose esters. All emulsions were produced by high-pressure homogenization (0.57 MPa, 5 passes) and then subjected to in vitro digestion under simulated conditions of the male or female gastrointestine. Digesta samples were analyzed via confocal microscopy and laser-based particle sizing, revealing that protein-stabilized emulsions were responsive to physiological differences between males and females, whereas emulsions stabilized by non-protein emulsifiers remained mostly unaffected by sex-based differences. Absolute differential analyses of emulsion droplet size-distribution curves showed that changes in breakdown trajectories for emulsions were pronouncedly noticeable in gastric effluents. Further, SDS-PAGE analysis of digesta showed that breakdown patterns of protein-stabilized emulsions are consistent with prior evidence found for healthy adults; however, results under female gut conditions indicated variations in protein clotting that may alter bioaccessible levels of bioactive peptides. Thus, this study underscores the importance of considering consumer biological sex in food design, especially regarding emulsion-based products for targeted digestive responses.